Diagnostic Performance of Multiple Sound Touch Elastography for Differentiating Benign and Malignant Thyroid Nodules - Zhang, Lei; Ding, Zhimin; Dong, Fajin; Wu, Huaiyu; Liang, Weiyu; Tian, Hongtian; Ye, Xiuqin; Luo, Hui; Xu, Jinfeng (Frontiers in Pharmacology, 2018)
This study evaluated the ability of Sound Touch Elastography (STE) to distinguish malignant from benign thyroid nodules by quantifying tumor stiffness using the elastic ratio (EI) and shear modulus (G). Eighty-six patients with 86 nodules were enrolled in this study. There were 24/86 (27.90%) thyroid papillary carcinomas (TPC) and 62/86 (72.10%) benign nodules. The mean EI was significantly lower in TPCs than in benign nodules. The EI area under the receiver operating characteristic curve (ROC) was 80%. The EI cutoff value for TPCs was 0.215%. The sensitivity (Sen), specificity (Spe), positive likelihood ratio (LR+), and negative likelihood ratio (LR-) were 71%, 73%, 2.58, and 0.40, respectively. Gmax, Gmean, and Gsd were significantly higher in TPCs than in benign nodules. There were no significant differences in Gmin. Compared with other G parameters, Gmax with an optimal cutoff value of 15.82 kPa had the highest AUROC value (84%). The Sen, Spe, LR+, and LR- were 79.17%, 79.03%, 3.776, and 0.261, respectively. We pooled the EI, Gmax, Gmean, and Gsd and the pooled-Sen, Spe, -LR+, LR-, diagnostic odds ratio, ​and odds ratio, and area under the summary ROC were 79%, 71%, 2.73,0.29, 2.23, 9.29, and 82%, respectively. STE could be a new ultrasound diagnostic method for evaluating benign and malignant thyroid nodules.